Disseminated fusariosis by Fusarium proliferatum in a patient with aplastic anaemia receiving primary posaconazole prophylaxis - case report and review of the literature - Ricna, Dita; Lengerova, Martina; Palackova, Martina; Hadrabova, Marketa; Kocmanova, Iva; Weinbergerova, Barbora; Pavlovsky, Zdenek; Volfova, Pavlina; Bouchnerova, Jana; Mayer, Jiri; Racil, Zdenek (Mycoses, 2016)
Disseminated fusariosis is a life-threatening, invasive, opportunistic infection in immunocompromised patients, especially those with haematological malignancies. The prognosis is poor because these fungi are resistant to many of the available antifungal agents. We present a case of disseminated fusariosis caused by Fusarium proliferatum in a patient with severe aplastic anaemia complicated by a secondary infection of Aspergillus flavus, with a fatal outcome. We also review the documented Fusarium infections in immunocompromised hosts.
Keywords: Triazoles; fusariosis; Fusarium; Aspergillosis; Anemia, Aplastic; Male; Opportunistic Infections; fusarióza; aspergilóza; mužské pohlaví; Fusariosis; Aspergillus flavus; Antifungal Agents; mladý dospělý; Fatal Outcome; antifungální látky; oportunní infekce; Young Adult; triazoly; Humans; koinfekce; Fusarium proliferatum; Immunocompromised Host; aplastická anemie; PCR diagnostics; Coinfection; real-time PCR; fatální výsledek; lidé; imunokompromitovaný pacient